Fast method for 1D non-cartesian parallel imaging using GRAPPA - Heidemann, Robin M.; Griswold, Mark A.; Seiberlich, Nicole; Nittka, Mathias; Kannengiesser, Stephan A.R.; Kiefer, Berthold; Jakob, Peter M. (Magnetic resonance in medicine, 2007)
MRI with non‐Cartesian sampling schemes can offer inherent advantages. Radial acquisitions are known to be very robust, even in the case of vast undersampling. This is also true for 1D non‐Cartesian MRI, in which the center of k‐space is oversampled or at least sampled at the Nyquist rate. There are two main reasons for the more relaxed foldover artifact behavior: First, due to the oversampling of the center, high‐energy foldover artifacts originating from the center of k‐space are avoided. Second, due to the non‐equidistant sampling of k‐space, the corresponding field of view (FOV) is no longer well defined. As a result, foldover artifacts are blurred over a broad range and appear less severe. The more relaxed foldover artifact behavior and the densely sampled central k‐space make trajectories of this type an ideal complement to autocalibrated parallel MRI (pMRI) techniques, such as generalized autocalibrating partially parallel acquisitions (GRAPPA). Although pMRI can benefit from non‐Cartesian trajectories, this combination has not yet entered routine clinical use. One of the main reasons for this is the need for long reconstruction times due to the complex calculations necessary for non‐Cartesian pMRI. In this work it is shown that one can significantly reduce the complexity of the calculations by exploiting a few specific properties of k‐space‐based pMRI. Magn Reson Med 57:1037–1046, 2007. © 2007 Wiley‐Liss, Inc.